Seed storage: maintaining seed viability and vigor for restoration use. (26th May 2020) - De Vitis, Marcello; Hay, Fiona R.; Dickie, John B.; Trivedi, Clare; Choi, Jaeyong; Fiegener, Rob
Abstract : Effective seed storage after sourcing (harvesting or purchasing) is critical to restoration practitioners and native seed producers, as it is key to maintaining seed viability. Inadequate seed storage can lead to a waste of both natural and economic resources when seeds of poor quality are sown. When working with native species with unknown storage behavior, general assumptions can be made based on studies on related species, and standard practices may be applied with caution; however, an investigation should be conducted to understand if specific storage requirements are needed and for how long seeds can be stored before they lose significant viability. In this paper of the Special Issue Standards for Native Seeds in Ecological Restoration, we provide an overview of the key concepts in seed storage and the steps to take for effective storage of native seeds for restoration use.